EXPLORING PERSONALIZED LEARNING FEATURES IN AN EFL CLASSROOM: A CASE IN INDONESIAN HIGHER EDUCATION - Ignasia Yuyun; Nenden Sri Lengkanawati; Ika Lestari Damayanti; Fazri Nur Yusuf (University of Kuningan, 2025)
Leveraging a learner-centered approach in higher education is a prerequisite to complying with the current Indonesian curriculum policy, which promotes student mobility and seamless learning. Thus, implementing personalized learning in the classroom supports learning flexibility by accommodating students' needs, preferences, and interests and promotes student agency. Considering the limited implementation of personalized learning in EFL classrooms, this study aims to investigate how personalized learning features support EFL student learning, particularly in online synchronous and asynchronous EFL classrooms, which has the potential to inspire future research. Through a writing playlist facilitated by a learning management system, this study employed class observations and focus group discussions involving ten senior students in the English Department. It reveals that personalized learning features, including goal setting, learning tracking, learning phases/instructions, learning support/collaboration, assessment (self-peer-teacher), self-reflection, and voice and choice (flexibility), facilitate EFL students in making, participating in, contributing to, and managing their learning. In light of these findings, this study suggests incorporating more digital technologies to leverage and monitor the success of implementing personalized learning in Indonesian English as a Foreign Language (EFL) classrooms. In addition, involving more participants and other English skill classes could enhance the overall depth and breadth of the research findings.